2016
DOI: 10.4103/0970-9185.168159
|View full text |Cite
|
Sign up to set email alerts
|

Phenylephrine infusion for spinal-induced hypotension in elective cesarean delivery: Does preload make a difference?

Abstract: Background and Aims:Patients undergoing elective cesarean delivery (CD) have a high-risk of spinal-induced hypotension (SIH). We hypothesized that a colloid preload would further reduce SIH when compared with a crystalloid preload.Material and Methods:Eighty-two healthy parturients undergoing elective CD were included in the study. Patients were randomly assigned to two groups (41 patients in each group) to receive either Lactated Ringer's solution (1500 ml) or hydroxyethyl starch (6% in normal saline, 500 ml)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Fourth, phenylephrine infusion is frequently used to treat hypotension induced by spinal anesthesia in cesarean section [37, 38]. We excluded this group of patients because the indication and procedure are significantly different than general anesthesia and because of the prior observation that phenylephrine response in this group could be different [39, 40]. Future studies could include general or spinal anesthesia as distinct categories.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, phenylephrine infusion is frequently used to treat hypotension induced by spinal anesthesia in cesarean section [37, 38]. We excluded this group of patients because the indication and procedure are significantly different than general anesthesia and because of the prior observation that phenylephrine response in this group could be different [39, 40]. Future studies could include general or spinal anesthesia as distinct categories.…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies reported the requirement of phenylephrine following spinal anesthesia induced hypotension. [ 39 , 44 ] A statistically significant reduction in phenylephrine requirement was observed with the use of colloid preloading compared with crystalloid preloading (standardized mean difference: -0.54, 95% CI: -0.82 to -0.25; 169 women; I 2 = 0%, P = .0002).…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of intraoperative nausea and/or vomiting was reported in 20 trials. [ 15 , 17 , 20 , 23 , 24 , 26 , 27 , 29 , 30 , 32 35 , 37 , 39 – 42 , 44 , 47 ] Among these trials, a statistically significant reduction in nausea and/or vomiting was found when colloid preloading was administered compared with crystalloid preloading (risk ratio: 0.72, 95% CI: 0.55–0.95; 1601 women; P = .02; Fig. 5 ) with mild heterogeneity ( I 2 = 36%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations